2010
DOI: 10.1177/0266242610363521
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of the effectiveness of occupational health and safety management systems in SMEs

Abstract: This article analyses the effectiveness of occupational health and safety (OHS) management in small and medium-sized enterprises (SMEs). In particular, we (1) provide an overview of the implementation of occupational risk preventive activities in a sample of SMEs; (2) characterize alternative approaches of OHS management systems; (3) assess the effectiveness of the identified OHS systems in occupational safety outcomes; and (4) analyse the factors affecting the adoption of such OHS systems. The study is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 24 publications
2
44
0
1
Order By: Relevance
“…Aziz et al (2015) reported that during 2010and http://dx.doi.org/10.15405/epsbs.2016.08.120 eISSN: 2357-1330 Selection and peer-review under responsibility of the Organizing Committee 857 2012, between 80 and 90 percent of occupational accidents were reported in SMEs in Malaysia. In this regard, Malaysia is not unique because SMEs in other countries, such as Europe, are 4.9 times likely to experience fatal industrial accidents (Arocena & Nunez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Aziz et al (2015) reported that during 2010and http://dx.doi.org/10.15405/epsbs.2016.08.120 eISSN: 2357-1330 Selection and peer-review under responsibility of the Organizing Committee 857 2012, between 80 and 90 percent of occupational accidents were reported in SMEs in Malaysia. In this regard, Malaysia is not unique because SMEs in other countries, such as Europe, are 4.9 times likely to experience fatal industrial accidents (Arocena & Nunez, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The enterprise needs to guarantee regular health checkups in accordance with the risks at work (Arocena & Núñez, 2010;Cagno, Micheli, Jacinto, & Masi, 2014).…”
Section: Productionmentioning
confidence: 99%
“…Size of the companies: Lin and Mills (2001), Holmes (1999), Lingard and Rowlinson (1994) concede that size of the companies is one of the major factors which affects the probability of accidents on site. Previous research shows that there are higher accident rates in small and medium-sized enterprises (SMEs) as compared with the larger ones (Arocena andNúñez 2010 andKongtip et al (2008). The problems faced by some of these companies include the lack of human resources, funds, limitation of technology and management (Kongtip et al 2008).…”
Section: Organizational Factormentioning
confidence: 99%